(untitled) (Physical Education, Health and Social Sciences, 2026)
The increase in demand for nutritionally balanced milk and milk products is due to increasing awareness and scientific evidence of the functional and nutritional properties of milk. The quality and shelf life of dairy products and their yield are directly affected by the composition and properties of raw milk. Variations occur in raw milk quality due to various factors, such as intrinsic factors, which are breed and genotype, lactation stages, age, and the size of the animal, and extrinsic factors, which include season, climatic conditions, change in the feeding system, herd management, and farm management practices. This research aimed to study the effect of different cows and buffalos with feeding patterns and variations on raw milk composition. Quality indicators of raw milk such as pH, acidity, protein, fat, SNF (Solid Not Fat), total solids, BR values, and microbial analysis such as total plate count (TPC) and total coliform count (TCC) were analyzed to explore the variation in milk quality between cows and buffalos. Milk samples were collected in sterilized glass bottles to check variations in milk composition with variations in feed and region of different breeds of cow and buffalo from dairy farms in the southern and central areas of Punjab. Data were analyzed statistically to compare the means of each parameter. The results revealed that the percentage of fat, protein, and total solids of milk varied significantly between cows and buffalos. The result indicated a significant difference in the content of fat. The fodder that was used, such as sorghum millet and maize, and generally dairy cattle were grazed in green pastures, had more fat. Animals that were fed on mustard, rapeseed, berseem, lucern, sugarcane, and oat had more LR, BR, and pH; similarly, those fed on soybean meal had high protein content. The animals that fed on fresh grass had more total solids (TS), solid not fat (SNF), and protein.